A Perspective on the Use of FVIII Concentrates and Cryoprecipitate Prophylactically in Surgery or Therapeutically in Severe Bleeds in Patients with von Willebrand Disease Unresponsive to DDAVP: Results of an International Survey - Foster, Paul A (Thrombosis and Haemostasis, 1995)
An international registry was established by the Subcommittee on von Willebrand Factor of the SSC/ISTH on the treatment of patients with types of von Willebrand disease (vWd) unresponsive to DDAVP infusion. Data was collected on 76 surgical events in 64 patients from 19 treatment centers. Thirty-three non-mucosal, 12 mucosal, 10 orthopedic and 21 dental procedures were reported. In the 76 surgical events, 14 cases prophylactically received cryoprecipitate while 62 received factor VIII (FVIII) concentrate. Surgical hemostasis was reported as satisfactory, good, or excellent in 75 of the 76 cases. Post-infusion bleeding times were measured in only three of 14 surgical events treated with cryoprecipitate. All three cases had a reduction but not correction of the bleeding time. The post-infusion bleeding time was measured in 27 of 62 cases in which FVIII concentrates were used. The bleeding time was normalized in 15, reduced but not normalized in eight, and not changed from baseline in four. Data was also collected from 16 treatment centers on 50 serious bleeding events in 35 patients. These included 19 gastrointestinal, 15 other mucosal, four central nervous system, seven orthopedic, and five other bleeds. Eleven cases received cryoprecipitate and 39 received FVIII concentrate as primary therapy. The efficacy of treatment was considered good or excellent in 49 of 50 cases. Post-infusion bleeding times were measured in only 15 of the 50 reported bleeding events. The post-infusion bleeding time was normalized in six, decreased but not normalized in eight, and not changed from baseline in one. In this retrospective survey, FVIII concentrates were subjectively as efficacious as cryoprecipitate in both the surgical setting and for the treatment of severe bleeds in patients with types of vWd unresponsive to DDAVP. Since the bleeding time was monitored during therapy in only a minority of these cases, a definitive relationship between the efficacy of therapy and normalization or reduction of the bleeding time in these two clinical settings cannot be established from this study. A prospective study on the use of FVIII and/or vWf concentrates in these clinical settings is necessary to address this issue.